2013
DOI: 10.1373/clinchem.2012.200543
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Degradation Pattern of Cardiac Troponin T Following Myocardial Infarction

Abstract: BACKGROUND Cardiac troponin T (cTnT) is widely used for the diagnosis of acute myocardial infarction (AMI). However, it is still unclear whether degraded cTnT forms circulate in the patient's blood. We therefore aimed to elucidate which cTnT forms are detected by the clinical assay. METHODS Separation of cTnT forms by gel filtration chromatography (GFC) was performed in sera from 13 AMI patients to examine cTnT degradation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 33 publications
2
55
0
1
Order By: Relevance
“…However, based on their molecular weight, free cTnT (37 kDa), free cTnI (24 kDa), and their fragments may be (partly) filtered by the glomeruli and catabolized by the tubules (25,26 ). Indeed, after myocardial infarction, cTnT and cTnI have been observed as free cTnT and cTnI, larger cTnT-I-C (77 kDa) and cTnI-C (40 kDa) complexes, and fragments (27)(28)(29)(30)(31). In contrast, in renal failure, cTnT circulates primarily as fragments (32 ), whereas the circulating form of cTnI in renal failure is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on their molecular weight, free cTnT (37 kDa), free cTnI (24 kDa), and their fragments may be (partly) filtered by the glomeruli and catabolized by the tubules (25,26 ). Indeed, after myocardial infarction, cTnT and cTnI have been observed as free cTnT and cTnI, larger cTnT-I-C (77 kDa) and cTnI-C (40 kDa) complexes, and fragments (27)(28)(29)(30)(31). In contrast, in renal failure, cTnT circulates primarily as fragments (32 ), whereas the circulating form of cTnI in renal failure is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that the fast clearance of Myo and CK may result from extensive local degradation, because many clinical assays do not detect degraded CK. In contrast, the clinical cTnT assay recognizes several degradation products (20 ) that could prolong the apparent clearance of cTnT.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since cTnI and cTnT are present in the sarcomeric complex in a molecular ratio of 1:1, these differences between the circulating cTns are probably related to differences in intra- [130] or extra-cellular [131][132][133] catabolism and the peripheral turnover of cTnI and cTnT. A recent study [134] found that circulating levels of cTnT, unlike cTnI, have a diurnal rhythm, thus bearing out the hypothesis that there are some differences in the release from cardiomyocytes and/or peripheral turnover between cTnI and cTnT.…”
Section: Do Differences In Troponin-dependent 99th Url Values Depend mentioning
confidence: 99%